Internal breast dosimetry in mammography: Experimental methods and Monte Carlo validation with a monoenergetic x‐ray beam. Issue 4 (23rd February 2018) - Fedon, Christian; Caballo, Marco; Longo, Renata; Trianni, Annalisa; Sechopoulos, Ioannis
Abstract : Purpose: To investigate the performance, such as energy dependence and sensitivity, of thermoluminescent dosimeters (TLD), metal oxide semiconductor field‐effect transistor dosimeters (MOSFET), and GafChromic™ films, and to validate the estimates of local dose deposition of a Monte Carlo (MC) simulation for breast dosimetry applications. Methods: Experimental measurements were performed using a monoenergetic beam at the ELETTRA synchrotron radiation light source (Trieste, Italy). The three types of dosimeters were irradiated in a plane transversal to the beam axis and calibrated in terms of air kerma. The sensitivity of MOSFET dosimeters and GafChromic™ films was evaluated in the range of 18–28 keV. Three different calibration curves for the GafChromic™ films were tested (logarithmic, rational, and exponential functions) to evaluate the best‐fit curve in the dose range of 1–20 mGy. Internal phantom dose measurements were performed at 20 keV for four different depths (range 0–3 cm, with 1 cm steps) using a homogeneous 50% glandular breast phantom. A GEANT4 MC simulation was modified to match the experimental setup. Thirty sensitive volumes, on the axial‐phantom plane were included at each depth in the simulation to characterize the internal dose variation and compare it to the experimental TLD and MOSFET measurements. Experimental 2D dose maps were obtained with the GafChromic™ films and compared to the simulated 2D dose distributions estimated with the MC simulations. Results: The sensitivity of the MOSFET dosimeters and GafChromic™ films increased with x‐ray energy, by up to 37% and 48%, respectively. Dose–response curves for the GafChromic™ film result in an uncertainty lower than 5% above 6 mGy, when a logarithmic relationship is used in the dose range of 1–10 mGy. All experimental values fall within the experimental uncertainty and a good agreement (within 5%) is found against the MC simulation. The dose decreased with increasing phantom depth, with the reduction being 80% after 3 cm. The uncertainty of the empirical measurements makes the experimental values compatible with a flat behavior across the phantom slab for all the investigated depths, while the MC points to a dose profile with a maximum toward the center of the phantom. Conclusions: The calibration procedures and the experimental methodologies proposed lead to good accuracy for internal breast dose estimation. In addition, these procedures can be successfully applied to validate MC codes for breast dosimetry at the local dose level. The agreement among the experimental and MC results not only shows the correctness of the empirical procedures used but also of the simulation parameters.